Perceiving Mining Management from Qur`anic Perspective: A Tafsir Maqāṣidi Analysis in Indonesian Framework - Alfi, Ahmad Musonnif; Ramadhan, Achmad Farkhan; Muthoharoh, Muthoharoh; Panandang, Uta; Nawwaf, Aufa Varrassyah (Taqaddumi: Journal of Quran and Hadith Studies, 2024)
Lately, the mining issue in Indonesia has become controversial due to the regulation of the President of Indonesia Number 76 of 2004. The studies focusing on the issue of mining and its connection with the Qur`an have not existed at all. So far, articles on mining issues have been merely descriptive, not applicative. Hence, this article aims to contextualize the Qur`an with mining operations in Indonesia. This article is qualitative research and utilizes al-tafsīr al-maqāṣidī as the approach. By examining the maqāṣid of the Qur`anic verse, this article reveals that managing the earth to obtain its benefits is allowed as it is a natural thing given by God while maintaining the sustainability of the environment as well as complying with sharia. In addition, government’s regulations have been compatible with the maqāṣid as well.